1997
DOI: 10.1176/jnp.9.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Subjective complaints versus actual cognitive deficits in predominantly symptomatic HIV-1 seropositive individuals

Abstract: The relationship of self-reported cognitive, motor, and affective complaints to actual neuropsychological functioning was explored in a cohort of predominantly symptomatic HIV-1 seropositive individuals. Ninety-two symptomatic HIV-1 infected subjects were questioned about complaints common in HIV infection and were assessed with a comprehensive neuropsychological test battery. No relationship was found between subjective complaints and cognitive functioning, yet a significant relationship was found between sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Accordingly, symptoms of depression were associated with disease conviction, dysphoria and irritability. These data are consistent with previous research suggesting that HIV-infected patients with depression show inadequate ways of reacting to their physical status [16, 17, 18]. Nevertheless, in contrast to studies of patients with non-HIV physical illnesses [10, 11, 13, 15], hypochondriac traits were not found to be associated with psychological stress symptoms or depression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Accordingly, symptoms of depression were associated with disease conviction, dysphoria and irritability. These data are consistent with previous research suggesting that HIV-infected patients with depression show inadequate ways of reacting to their physical status [16, 17, 18]. Nevertheless, in contrast to studies of patients with non-HIV physical illnesses [10, 11, 13, 15], hypochondriac traits were not found to be associated with psychological stress symptoms or depression.…”
Section: Discussionsupporting
confidence: 89%
“…The authors suggested that HIV-positive subjects prone to depression were more cognizant of bodily symptoms and, thus, tended to perceive and interpret normal physical symptoms as indicators of an ineluctable and rapid progression of their illness. Likewise, complaints about impairment in motor and cognitive functions, not substantiated by physical and neuropsychological examination, as well as complaints about somatic symptoms in HIV patients without AIDS were associated with depression [17, 18]. In line with these studies, it has been shown that improvement in physical conditions is not necessarily followed by improvement in depressive symptoms in HIV-infected patients [19].…”
Section: Introductionmentioning
confidence: 97%
“…Among the factors most often discussed are the effects of mood and depressive symptoms on self ratings (Moore et al, 1997; Rabbitt & Abson, 1990, 1991; Simon & Bjork, 2001). Here, we used a mean CFQ score, reflecting an overall level of cognitive complaints over time, which may be less sensitive to temporal variability in mood and cognitive complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Although those who candidly admit to poor adherence to their prescribed medication regimens may be accurately reporting their behavior, several studies have demonstrated that patients who self-report perfect or near-perfect adherence may be overestimating by 10–20% (Arnsten et al, 2001; Levine et al, 2006). The lack of association between objective findings and subjective ratings has been addressed in previous investigations and has been explained by psychiatric factors (Hinkin et al, 1996; Moore, van Gorp, Hinkin, Stern, & Swales, 1997; Rourke, Halman, & Bassel, 1999), impaired cognition (Reinhard et al, 2007), and poor insight (Gazelle et al, 2007). Given the limited validity of self-report of functional decline, it is now becoming increasingly common to incorporate performance-based tasks to assess functional abilities in HIV, since they have been shown to be more reliable and objective measures of “real-world” performance (Heaton et al, 2004a).…”
Section: Introductionmentioning
confidence: 96%